(untitled) (REMUNOM, 2025)
The most recent concept of schizophrenia indicates a chronic idiopathic psychosis, indicating that it is a set of different diseases with similar and overlapping symptoms. In this sense, the objective of the present study is to analyze the main challenges faced by schizophrenic patients and their caregivers, aiming to develop pertinent proposals for the prevention of progressive damage, psychomotor and cognitive rehabilitation, in order to minimize social and communication impairments. This is a bibliographic study, of the systematic review type, and the technical support was obtained from the Scielo, Lilacs, BVS and Google Scholar databases. The data were presented in text and the conclusion was that schizophrenia affects not only health, but also the patient’s cognition, function, autonomy and independence.